If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x-3)-5=-11
We move all terms to the left:
3(x-3)-5-(-11)=0
We add all the numbers together, and all the variables
3(x-3)+6=0
We multiply parentheses
3x-9+6=0
We add all the numbers together, and all the variables
3x-3=0
We move all terms containing x to the left, all other terms to the right
3x=3
x=3/3
x=1
| 0=-2(4a+2)+5(2a+2) | | 3g=7=-2 | | 30+20=x-20 | | -3g=7+-2 | | P=2h+8 | | -2w+(-7)=-11 | | G=9/2(p-25) | | m/2-8=-7 | | -137=3n=5(-6n+5) | | 6x-5(4x+6)=6 | | a=196/20 | | u/9-(-90)=97 | | 5x+0.3=15.3 | | 14=u/5+13 | | 7-27x-3x=37 | | -2(x-4)+4=2(-x+6) | | r+4.1=11.4 | | g/4-(-13)=15 | | 30-5x=63x+7 | | 32x-4+10=3x-6+2x | | x/4+13=28 | | 22-3k=10 | | 21-2v=19 | | 57=-3d+6 | | 4-(-c)=1 | | 0.25x+30=0.15x+45 | | -16+13+-20x+23=180 | | 5|y-1|=-20 | | 10-7x=-3(x+6) | | -0.05+0.8=0.2y-1.6 | | .6x+4=2x | | (4+4)(5+3x)=60-5.5(x+5) |